Development of Children's Use of External Reminders for Hard‐to‐Remember Intentions. Issue 6 (15th February 2018) - Redshaw, Jonathan; Vandersee, Johanna; Bulley, Adam; Gilbert, Sam J.
Abstract : This study explored under what conditions young children would set reminders to aid their memory for delayed intentions. A computerized task requiring participants to carry out delayed intentions under varying levels of cognitive load was presented to 63 children (aged between 6.9 and 13.0 years old). Children of all ages demonstrated metacognitive predictions of their performance that were congruent with task difficulty. Only older children, however, set more reminders when they expected their future memory performance to be poorer. These results suggest that most primary school‐aged children possess metacognitive knowledge about their prospective memory limits, but that only older children may be able to exercise the metacognitive control required to translate this knowledge into strategic reminder setting.